A multicriteria optimization framework for the definition of the spatial granularity of urban social media analytics. Issue 1 (2nd January 2021) - de Andrade, Sidgley Camargo; Restrepo-Estrada, Camilo; Nunes, Luiz Henrique; Rodriguez, Carlos Augusto Morales; Estrella, Júlio Cézar; Delbem, Alexandre Cláudio Botazzo; Porto de Albuquerque, João
ABSTRACT: The spatial analysis of social media data has recently emerged as a significant source of knowledge for urban studies. Most of these analyses are based on an areal unit that is chosen without the support of clear criteria to ensure representativeness with regard to an observed phenomenon. Nonetheless, the results and conclusions that can be drawn from a social media analysis to a great extent depend on the areal unit chosen, since they are faced with the well-known Modifiable Areal Unit Problem. To address this problem, this article adopts a data-driven approach to determine the most suitable areal unit for the analysis of social media data. Our multicriteria optimization framework relies on the Pareto optimality to assess candidate areal units based on a set of user-defined criteria. We examine a case study that is used to investigate rainfall-related tweets and to determine the areal units that optimize spatial autocorrelation patterns through the combined use of indicators of global spatial autocorrelation and the variance of local spatial autocorrelation. The results show that the optimal areal units (30 km 2 and 50 km 2 ) provide more consistent spatial patterns than the other areal units and are thus likely to produce more reliable analytical results.